(untitled) - Harbison, Samuel P. (Englewood Cliffs, N.J., 1987)
Contents: The C language; Lexical elements; The C preprocessor; Declarations; Conversions and representations; Program structure; Standard language additions...
Keywords: C (Computer program language),C (Ngôn ngữ chương trình vi tính)